2004
DOI: 10.1016/s1056-8727(03)00019-9
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of polymorphisms in UCP1-3 genes for diabetic nephropathy

Abstract: Increased production of reactive oxygen species (ROS) has been suggested as a cause of diabetic complications. Uncoupling proteins (UCPs) have been ascribed a role in reducing the formation of ROS, and genetic variation in genes encoding for UCPs could thus be putative candidate genes for diabetic nephropathy. To test this hypothesis we searched for association between the A ! G ( À 3862) variant in UCP1, the insertion/deletion (I/D) polymorphism in exon 8 in UCP2, and the C ! T ( À 55) polymorphism in UCP3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Notwithstanding, other studies have reported that this polymorphism is not individually associated with basal metabolic rate, metabolic syndrome, BMI, obesity, insulin secretion or T2DM [27], [35], [38], [55], [56], [57], [58]. The T allele of the UCP3 -55C/T polymorphism has been associated with increased incidence of T2DM [59], higher BMI [60], [61], lower BMI [62], [63], higher HDL cholesterol levels [62], larger waist circumference [64], and high total cholesterol and LDL cholesterol levels and reduced risk of T2DM [31]. However, other studies have not found associations between this polymorphism and metabolic rate, obesity, BMI, insulin secretion or T2DM [55], [57], [65], [66], [67].…”
Section: Discussionmentioning
confidence: 90%
“…Notwithstanding, other studies have reported that this polymorphism is not individually associated with basal metabolic rate, metabolic syndrome, BMI, obesity, insulin secretion or T2DM [27], [35], [38], [55], [56], [57], [58]. The T allele of the UCP3 -55C/T polymorphism has been associated with increased incidence of T2DM [59], higher BMI [60], [61], lower BMI [62], [63], higher HDL cholesterol levels [62], larger waist circumference [64], and high total cholesterol and LDL cholesterol levels and reduced risk of T2DM [31]. However, other studies have not found associations between this polymorphism and metabolic rate, obesity, BMI, insulin secretion or T2DM [55], [57], [65], [66], [67].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have pointed out T2DM association of genetic variants both in nDNA-encoded mitochondrial genes (Krempler et al 2002; Muller et al 2003; Lindholm et al 2004; Wang et al 2004) and in mtDNA (Poulton et al 2002; Guo et al 2005; Mohlke et al 2005; Fuku et al 2007; Nishigaki et al 2007; Feder et al 2009; Achilli et al 2011). However, many of these studies assessed the disease association of variants either within the nDNA or in the mtDNA, thus overlooking the impact of mitonuclear interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training with dietary counseling increases mitochondrial HSP60 and glucose-regulated protein 75 (GRP75) expression in skeletal muscle in middle-aged subjects with impaired glucose tolerance [68], suggesting a protective role of HSP60, or possibly the UPR mt in glucose metabolism and antioxidative capacity. In addition to metabolic dysregulation, mitochondrial stress and/or impairment in the UPR mt pathway such as reducing the expression levels or activities of mitochondrial chaperones has also been implicated in neurological diseases and sporadic diseases of aging [32, 6971]. …”
Section: Mitochondrial Stress and Unfolded Protein Responsementioning
confidence: 99%